2021
DOI: 10.1039/d1tc00632k
|View full text |Cite
|
Sign up to set email alerts
|

Lead-free MnII-based red-emitting hybrid halide (CH6N3)2MnCl4 toward high performance warm WLEDs

Abstract: Environmental friendly metal hybrid halides show great promise for white light emitting diode (WLED) applications due to their unique optical properties. Herein, a lead-free blue-light excited red-emitting Mn2+-based hybrid halide...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
97
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(104 citation statements)
references
References 38 publications
7
97
0
Order By: Relevance
“…A 1 (S)) of four coordinated [MnBr 4 ] 2À units. The lifetime value of (CH 6 N 3 ) 2 MnBr 4 has not been proven, but compared with the similar A 2 BX 4 type Mn 2+ -based chlorides, 42,43 its lifetime value is smaller, which is in line with the law of the influence of halogen ions on the lifetime in green-emitting Mn 2+ -based halides. 15 Accordingly, the red emission peaked at 627 nm is attributed to the d-d transition ( 4 T 1 (G) -6 A 1 (S)) of six coordinated [Mn 3 Br 12 ] 6À units.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…A 1 (S)) of four coordinated [MnBr 4 ] 2À units. The lifetime value of (CH 6 N 3 ) 2 MnBr 4 has not been proven, but compared with the similar A 2 BX 4 type Mn 2+ -based chlorides, 42,43 its lifetime value is smaller, which is in line with the law of the influence of halogen ions on the lifetime in green-emitting Mn 2+ -based halides. 15 Accordingly, the red emission peaked at 627 nm is attributed to the d-d transition ( 4 T 1 (G) -6 A 1 (S)) of six coordinated [Mn 3 Br 12 ] 6À units.…”
mentioning
confidence: 60%
“…40,41 In addition, the 0D Mn 2+based OIMHs with a highly efficient red emission have also been reported and popularized recently. However, only a small amount of 0D Mn 2+ -based OIMHs that can emit red light was investigated so far, 3,24,42,43 and there is no comparative analysis of their luminescence mechanism by binding to that of 0D Mn 2+ -based OIMHs with green light emission.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of 0D Mn 2+ -based/Mn 2+ -doped halides have been reported, resulting in green-light emissions and red-light emissions, respectively. ,, In this work, we emphasize and investigate the synthesis methods, crystal structure, and PL characteristics of 0D Mn 2+ -based halides with narrow-band green emissions. It is worth noting that the halogen atoms and subtle changes in crystal structure will become factors in regulating the fluorescence emission peak position (500–550 nm), emission line widths (40–60 nm), and lifetimes (the shortest for iodides, the second for bromides, and the longest for chlorides) by influencing the ligand-field effects and nephelauxetic effects. , Moreover, Xia et al and Seshadri et al have discussed in depth the tuning relationship between the crystal structure and luminescence performances and found that a sufficiently long Mn···Mn distance enables all Mn 2+ centers to emit spontaneously, thereby leading to near-unity narrow-band green-light emissions in 0D Mn 2+ -based halides. , Even though most Mn 2+ -based emitters were applied as green-light components in LCD backlight and similar 0D Mn 2+ -based halides show a good application prospect in the field of solid-state displays, an easy-to-operate and large-scale synthesis method has not been proposed, and the characteristics of ultrafast self-assembly have not yet been fundamentally unraveled.…”
Section: Introductionmentioning
confidence: 99%
“…Mn 2+ is a commonly used dopant for altering magnetic, electrical and optical properties of materials. Introduction of Mn 2+ into perovskite host lattice significantly increases the stability and luminescence performance of the crystal structure. Due to the advantages of low toxicity and high abundance of Mn as well as the Mn 2+ d–d transition with emission featuring a large Stokes shift and long excited state lifetime, Mn 2+ has been considered as an efficient light emission center in metal halide perovskites . Replacing Pb 2+ with Mn 2+ to obtain Mn-based perovskites, including organic–inorganic hybrid and all-inorganic manganese-based perovskites, has been studied in recent years. , For Mn-based perovskites, the absorption and emission of Mn 2+ are strongly dependent on its coordination environment and the distance between the Mn 2+ ions .…”
mentioning
confidence: 99%
“…Mn 2+ is a commonly used dopant for altering magnetic, electrical and optical properties of materials. Introduction of Mn 2+ into perovskite host lattice significantly increases the stability and luminescence performance of the crystal structure. Due to the advantages of low toxicity and high abundance of Mn as well as the Mn 2+ d–d transition with emission featuring a large Stokes shift and long excited state lifetime, Mn 2+ has been considered as an efficient light emission center in metal halide perovskites . Replacing Pb 2+ with Mn 2+ to obtain Mn-based perovskites, including organic–inorganic hybrid and all-inorganic manganese-based perovskites, has been studied in recent years. , For Mn-based perovskites, the absorption and emission of Mn 2+ are strongly dependent on its coordination environment and the distance between the Mn 2+ ions . The tetrahedral coordination Mn 2+ shows a green emission (500–550 nm) with narrow full width at half-maximum (fwhm) (25–60 nm) while the octagonal coordination Mn 2+ shows an orange-red emission (>600 nm) with broad fwhm (>60 nm). , Nevertheless, the d–d transition of Mn 2+ , determined by spin and parity selection rules, is concentration-dependent with Mn–Mn coupling at high concentrations resulting in low photoluminescence quantum yield (PLQY) .…”
mentioning
confidence: 99%